PUAR: Performance and Usage Aware Routing Algorithm for Long and Linear Wireless Sensor Networks - Bin He; Gang Li (International Journal of Distributed Sensor Networks, 2014)
Aiming at requirements of performance and usage in the monitoring of tunnels with the long and linear structure, this work demonstrates a low-energy and quality of service- (QoS-) supported uneven clustering routing algorithm based on the labor cost called PUAR. PUAR realizes uneven clusters by a designed cluster radius related to the distance and the labor cost, with consideration of the residual energy and spatial layout of sensor nodes in the cluster head selection. With QoS support, PUAR uses the quality of link to reduce the packet loss and shortens the total transmitting distance to reduce the average delivery delay in multihop transmission. For the usage requirements of tunnel monitoring, PUAR utilizes the labor cost of replacing batteries to realize local or global energy balance. According to the analysis and simulation results, PUAR is found to achieve low-power consumption and reliable QoS support, and it can also reduce the operating cost of tunnel monitoring.